Stress and Coping Mechanism among the Parents of Intellectual Disable Children - Takuri, Bhawani Shahi (Journal of Advanced Academic Research, 2017)
Background: High perceived stress levels and lack of effective coping skills could be a barrier to achieve the challenges of parenting process. Objectives: The study was conducted to find out the level of stress and coping strategies used by the parents of intellectual disable children. Methodology: A descriptive cross sectional quantitative research design was adopted among 100 respondents from three organizations. The study was conducted by using a Perceived Stress Index and Coping Inventory tools in Kathmandu valley. Result: It showed that three forth of parents had severe stress to clinical significant stress level during their parenting process. Parents were used to cope up stress by using various coping strategies like use of instrumental social support, positive reinterpretation and growth, planning, suppression of competing activities and use of emotional social support. Conclusion: Health educators should find out the most stressful areas and give a serious thought to encourage the use of healthy coping strategies to improve their parenting process.